The F4/AS01B HIV-1 Vaccine Candidate Is Safe and Immunogenic, But Does Not Show Viral Efficacy in Antiretroviral Therapy-Naive, HIV-1-Infected Adults: A Randomized Controlled Trial - Dinges, Warren; Girard, Pierre-Marie; Podzamczer, Daniel; Brockmeyer, Norbert H.; Garcia, Felipe; Harrer, Thomas; Lelievre, Jean-Daniel; Frank, Ian; De Verdiere, Nathalie Colin; Yeni, Guy-Patrick; Ortega Gonzalez, Enrique; Rubio, Rafael; et al. (Medicine, 2016)
The impact of the investigational human immunodeficiency virus type 1 (HIV-1) F4/AS01B vaccine on HIV-1 viral load (VL) was evaluated in antiretroviral therapy (ART)-naive HIV-1 infected adults.This phase IIb, observer-blind study (NCT01218113), included ART-naive HIV-1 infected adults aged 18 to 55 years. Participants were randomized to receive 2 (F4/AS01B_2 group, N = 64) or 3 (F4/AS01B_3 group, N = 62) doses of F4/AS01B or placebo (control group, N = 64) at weeks 0, 4, and 28. Efficacy (HIV-1 VL, CD4 T-cell count, ART initiation, and HIV-related clinical events), safety, and immunogenicity (antibody and T-cell responses) were evaluated during 48 weeks.At week 48, based on a mixed model, no statistically significant difference in HIV-1 VL change from baseline was demonstrated between F4/AS01B_2 and control group (0.073 log10 copies/mL [97.5% confidence interval (CI): -0.088; 0.235]), or F4/AS01B_3 and control group (-0.096 log10 copies/mL [97.5% CI: -0.257; 0.065]). No differences between groups were observed in HIV-1 VL change, CD4 T-cell count, ART initiation, or HIV-related clinical events at intermediate timepoints. Among F4/AS01B recipients, the most frequent solicited symptoms were pain at injection site (252/300 doses), fatigue (137/300 doses), myalgia (105/300 doses), and headache (90/300 doses). Twelve serious adverse events were reported in 6 participants; 1 was considered vaccine-related (F4/AS01B_2 group: angioedema). F4/AS01B induced polyfunctional F4-specific CD4 T-cells, but had no significant impact on F4-specific CD8 T-cell and anti-F4 antibody levels.F4/AS01B had a clinically acceptable safety profile, induced F4-specific CD4 T-cell responses, but did not reduce HIV-1 VL, impact CD4 T-cells count, delay ART initiation, or prevent HIV-1 related clinical events.
EVALuna2:13261